Pengaruh Pemanfaatan Akun Instagram @menjadimanusia.id Terhadap Kebutuhan Informasi Kesehatan Mental Followers - Sevilla, Vinta; Helya Tahani, Devara (Global Komunika : Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
The presence of technology in everyday life has facilitated human activities in communicating and sharing information. Instagram is a social media that can be used to disseminate information, one of which provides information about mental health. The Instagram account menjadimanusia.id is a psychology account that can be used as an alternative channel to fulfill various mental health information needs. The menjadimanusia.id account seeks to raise awareness about the importance of mental health to the Indonesian people. This study aims to determine the effect of using Instagram account menjadimanusia.id on mental health information needs using the Uses and Gratification model. The approach in this study uses explanatory quantitative with a survey method, with distributing questionnaires via Instagram Direct Message to 150 respondents who have been determined through purposive sampling technique. Data analysis techniques in this study include normality tests, correlation tests, simple linear regression tests, coefficient of determination tests, and hypothesis tests. The results of the study based on statistical tests that have been carried out provide results that the use of Instagram account menjadimanusia.id has a significant and positive effect on the mental health information needs of followers. This is proven through hypothesis testing where the significance value is 0.000 <0.005, which means Ha is accepted and Ho is rejected, and through the results of the correlation test obtained a value (r) of 0.849 which shows that there is a strong relationship between the variable use of media on fulfilling information needs